A self-assembling split aptamer multiplex assay for SARS-COVID19 and miniaturization of a malachite green DNA-based aptamer - Martin R． O'Steen; Dmitry M．Kolpashchikov (Sensors and Actuators Reports, 2022)
Multiplex assays often rely on expensive sensors incorporating covalently linked fluorescent dyes. Herein, we developed a self-assembling aptamer-based multiplex assay. This multiplex approach utilizes a previously established split aptamer sensor in conjugation with a novel split aptamer sensor based upon a malachite green DNA aptamer. This system was capable of simultaneous fluorescent detection of two SARS COVID-19-related sequences in one sample with individual sensors that possesses a limit of detection (LOD) in the low nM range. Optimization of the Split Malachite Green (SMG) sensor yielded a minimized aptamer construct, Mini-MG, capable of inducing fluorescence of malachite green in both a DNA hairpin and sensor format.